Strategies for counseling the dangers of smoking for health for students - Sormin, Rosmin (International Journal of Curriculum Development, Teaching and Learning Innovation, 2023)
This activity is a form of application in the Teacher Professional Education Program carried out by teachers throughout Indonesia. Based on the results of surveys, interviews and observations found student problems about the number of students who smoke and also obtained from the background of many families who smoke. Cigarettes not only affect the smoker but also those around the smoker who also get smoke from cigarettes. The high rate of smoking will also have an impact on the high rate of smoking-related diseases. Smoking habits can increase a person's chances of developing several diseases such as heart disease, cancer and lung disease and can even lead to death. Providing counseling to students of class XII IPA 3 SMA Negeri 1 Garoga about the dangers of smoking can reduce students' desire to smoke. The existence of this counseling will form a good attitude and action in maintaining personal health